2009
DOI: 10.1007/s11013-009-9145-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedical Syndromes and Treatment-Seeking Behavior among Mayan Refugees in Chiapas, Mexico

Abstract: This survey investigated the prevalence of ethnomedical syndromes and examined treatments and treatment-seeking in Mayan Guatemalans living in United Nations High Commissioner for Refugee (UNHCR) camps in Chiapas, Mexico. Methods included a rapid ethnographic assessment to refine survey methods and inform the cross-sectional survey, which also examined mental health outcomes; 183 households were approached for interview, representing an estimated 1,546 residents in five refugee camps and 93% of all households.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…Susto has also been described as a Mexican Folk Illness, a Culture-Bound Syndrome (CBS). In more recent studies it has been called a Culturally Affiliated Syndrome, a Latin American Folk Syndrome, a Latin American Folk Illness, a Traditional Ethnomedical Concept that is broadly recognized by groups of Latin America, an Ethnomedical Syndrome that displays symptoms consistent with post-traumatic stress disorder, anxiety and depression as well as representing Idioms of Distress, often associated with psychiatric disorders, among Hispanic-American migrants (Durá-Vilá et al) [4,33,[38][39][40][41][42].…”
Section: Embodied Memories Of a Traumamentioning
confidence: 99%
“…Susto has also been described as a Mexican Folk Illness, a Culture-Bound Syndrome (CBS). In more recent studies it has been called a Culturally Affiliated Syndrome, a Latin American Folk Syndrome, a Latin American Folk Illness, a Traditional Ethnomedical Concept that is broadly recognized by groups of Latin America, an Ethnomedical Syndrome that displays symptoms consistent with post-traumatic stress disorder, anxiety and depression as well as representing Idioms of Distress, often associated with psychiatric disorders, among Hispanic-American migrants (Durá-Vilá et al) [4,33,[38][39][40][41][42].…”
Section: Embodied Memories Of a Traumamentioning
confidence: 99%
“…Finally, the Latin American concept of nervios ("nerves"), which stems from social overburden and conflict and includes sadness, anger, sleep troubles, hopelessness (see [22-25]), seems not unlike Caribbean descriptions of the circumstances and symptoms of "chronic fright." Like the two Caribbean fright varieties, ataques de nervios , susto , and nervios share some etiologies and symptoms with posttraumatic stress disorder, anxiety and depression as recognized by the American Psychiatric Association (see [20,26,27]).…”
Section: Introductionmentioning
confidence: 99%
“…The articles reviewed indicate that the patients reporting having suffered Susto, Nervios or Ataques de Nervios present increased chances of having suffered depression, anxiety, panic disorders and PTSD 19,20,23,29,33,34,37 . However, the way these articles evaluate this is based on the reports of the individuals about their past, and so it carries the bias of memory and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies showed a relationship between posttraumatic stress disorder (PTSD) and Nervios/Ataques de Nervios 19,20,23,37 . Norris et al 20 studied Mexican victims of natural disasters, residents of Florida and Mexico itself, encoding the answers through consensus among different raters.…”
Section: Identification Of Comorbidities Among Individuals Affectementioning
confidence: 99%